Movements of a Polar Bear from Northern Alaska to Northern Greenland - Durner, George M.; Amstrup, Steven C. (ARCTIC, 1995)
Using satellite telemetry, we monitored the movements of an adult female polar bear (Ursus maritimus) as she traveled from the Alaskan Beaufort Sea coast to northern Greenland. She is the first polar bear known to depart the Beaufort Sea region for an extended period, and the first polar bear known to move between Alaska and Greenland. This bear traveled for four months across the polar basin and came within 2 degrees of the North Pole. During the first year following her capture, she traveled 5256 km. Evidence to suggest her use of maternity dens in northern Alaska and in northern Greenland demonstrates the potential for genetic exchange between two widely separate populations of polar bears. The long life spans of polar bears and the rarity of their long-range movements means the significance of interpopulation movement can be assessed after long-term monitoring of individuals.Key words: polar bear, Ursus maritimus, satellite telemetry, movements, Beaufort Sea, populations, Alaska, Greenland, polar basin En utilisant la télémétrie par satellite, on a suivi les déplacements d'une ourse polaire (Ursus maritimus) alors qu'elle allait de la côte de la mer de Beaufort en Alaska au Groenland septentrional. À notre connaissance, elle est la première des ours polaires à avoir quitté la région de la mer de Beaufort pour une longue période, et la première à s'être déplacée entre l'Alaska et le Groenland. Cette ourse a traversé le bassin polaire durant quatre mois et s'est approchée à moins de 2° du pôle Nord. Au cours de la première année suivant sa capture, elle a parcouru 5256 km. Des preuves suggérant qu'elle a utilisé les tanières de mise bas dans l'Alaska septentrional et dans le Groenland septentrional démontrent le potentiel d'échanges génétiques existant entre deux populations d'ours polaires séparées par une grande distance. La longévité importante des ours polaires et la rareté des déplacements lointains signifient que les déplacements entre diverses populations ne peuvent être évalués qu'après une ...